THE PREVENTION ALTERNATIVE OF FRAUD IN BUSINESS PRACTICES - Yuniarti, Rozmita Dewi; Fitriani, Indah; Heryana, Toni; Halimah, Lilim; Saputra, Cahya Annaas; Febriani, Devi (Jurnal Riset Akuntansi dan Keuangan, 2021)
The principle of balance in accounting reflects the similarity in value between the source and allocation of expenditure contained in the balance sheet. Balance in the Islamic point of view, not only is the balance reflected in the value of the currency, but rather emphasizes the fulfillment of Islamic sharia on both sides of the balance. Therefore, this study seeks to provide a strengthening of the principle of accounting balance in an Islamic perspective in order to prevent fraud in business practices in the form of a fraud prevention model that is focused on in-depth observation of the source of assets and how to allocate them based on muamalah fiqh. The research method used is a qualitative method involving informants who have an understanding of the fiqh of muamalah, business man, and academics in the field of Islamic economics which is analyzed by triangulation techniques.Â Keywords: Source of Assets, Expenditure Allocation, Muamalah Fiqh, Fraud PreventioÂ